Cornsilk Fly (suggested common name), Euxesta stigmatias Loew (Insecta: Diptera: Otitidae) - Gregg S. Nuessly; John L. Capinera (EDIS)
‘Cornsilk flies’ are attractive, medium to dark metallic green to black colored flies with distinctive wing patterns and wing flapping behavior. They are commonly found throughout Florida’s agricultural communities. Their normally saprophytic lifestyle belies their destructive nature when it comes to their preference for sweet corn ears. Four species of ‘cornsilk flies’ are known to attack corn in Florida: Chaetopsis massyla (Walker), Euxesta annonae (Fabricius), Euxesta eluta Loew, and Euxesta stigmatias Loew. This 8-page fact sheet was written by Gregg S. Nuessly and John L. Capinera and published by the UF Department of Entomology and Nematology, April 2013.